No proven causal relationship between solarium use and melanoma risk (22.02.2019): correspondance - Reichrath, Jörg; Pilz, Stefan; März, Winfried (Deutsches Ärzteblatt, 2019)
Based on current evidence, we would like to critically discuss the study’s finding that an estimated 892 (5%) melanomas are due to solarium (UV tanning bed) use (1), before far-reaching conclusions are drawn. The risk estimators come from an older...
Gesehen am 10.07.2019